Newly dated permafrost deposits and their paleoecological inventory reveal an Eemian much warmer than today in Arctic Siberia - L. Schirrmeister; M. C. Fuchs; T. Opel; A. Andreev; F. Kienast; A. Schneider; L. Nazarova; L. Frolova; S. Kuzmina; T. Kuznetsova; V. Tumskoy; H. Matthes; et al. (Climate of the Past, 2025)
In this study, we integrate geochronological, cryolithological, paleoecological, and modeling data to reconstruct the Last Interglacial (LIG) climate around the New Siberian Islands, revealing significantly warmer conditions compared to today. New luminescence dating of the lacustrine deposits mostly preserved in ice-wedge pseudomorphs of 1–3 m thickness along the Dmitry Laptev Strait indicates ages consistent with the LIG (Marine Isotope Stage (MIS) 5e). Analysis of plant macrofossils and of pollen and faunal records (beetles and chironomids) from these deposits suggests mean temperatures of the warmest month (MTWAs) of 10.3 to 12.9 °C, 9.0 ± 3.0 °C, 8 to 10.5 °C, and 9.4 to 15.3 °C for Bol'shoy Lyakhovsky and of 12.7 to 15.3 °C, 9.7 ± 2.9 °C, 8 to 14 °C, and 12.0–13.8 °C for Oyogos Yar. The fossil-beetle-based mutual climate range for mean temperatures of the coldest month is −34 to −26 °C for Bol'shoy Lyakhovsky and −38 to −26 °C for Oyogos Yar. Our chironomid-based reconstructions of water table depth suggest 1.7 to 5.6 m for Bol'shoy Lyakhovsky, while previous analysis suggested 1.1 to 3.3 m for Oyogos Yar. Pollen-based reconstruction of mean annual precipitation (MAP) suggests 271 ± 56 mm for Bol'shoy Lyakhovsky and 229 ± 22 mm for Oyogos Yar. The first-time application of clumped isotopes to permafrost-preserved biogenic calcite of ostracods and bivalves for Oyogos Yar reconstructed near-surface water temperatures of 10.3 ± 3.0 °C and bottom-water temperatures of 5.3 ± 1.5 °C in thermokarst lakes during summer. In summary, the analyzed proxies suggest summers warmer than today by 5.5 to 12.8 °C for Bol'shoy Lyakhovsky and by 0.2 to 7.5 °C for Oyogos Yar and winters warmer than today by up to 7.1 and 8.4 °C for Bol'shoy Lyakhovsky and Oyogos Yar, respectively. Modern mean annual precipitation values are within the uncertainty range of the reconstructions. Climate model simulations for the LIG from PMIP suggest MTWAs warmer than today for Bol'shoy Lyakhovsky (4.4 ± 1.0 °C compared to 2.5 °C) and colder than today for Oyogos Yar (4.5 ± 1.2 °C compared to 7.8 °C), underestimating the Eemian warming reconstructed from our multiple paleoecological proxies. The LIG warming mainly affected summer conditions, whereas modern and future warming will rather impact winter conditions. As the LIG annual mean temperature is often used as an analog for the future climate in the High Arctic, the proxy–model mismatch highlights the urgent need for more systematic quantitative proxy-based temperature reconstructions in the Arctic and more sophisticated Earth system models capable of capturing Arctic paleoenvironmental conditions.